Bioinspired catecholic flame retardant nanocoating for flexible polyurethane foams - Cho, Joon Hee; Vasagar, Vivek; Shanmuganathan, Kadhiravan; Jones, Amanda R.; Nazarenko, Sergei; Ellison, Christopher J. (Chemistry of Materials, 2015)
An efficient, environmentally friendly, and water-applied flame retardant surface nanocoating based on polydopamine (PDA) was developed for foamed materials such as polyurethane (PU). The PDA nanocoating, deposited by simple dip-coating in an aqueous dopamine solution, consists of a planar sublayer and a secondary granular layer structure that evolve together, eventually turning into a dense, uniform, and conformal layer on all foam surfaces. In contrast to flexible PU foams that are known to be highly flammable without flame retardant additives, micro combustion calorimetry (MCC) and thermogravimetric analysis (TGA) confirm that the neat PDA is relatively inflammable with a strong tendency to form carbonaceous, porous char that is highly advantageous for flame retardancy. By depositing nano coatings of PDA onto flexible PU foams, the flammability of the PU foam was significantly reduced with increasing coating thickness. For the thickest coating (3 days of PDA deposition), the foam quickly self-extinguished and its original shape was completely preserved after exposure to a flame in a torch burn test. In addition to the char forming ability of PDA, it is hypothesized that its catechol units likely scavenge nearby radicals that typically evolve additional fuel for the fire as they attack surrounding materials. This multiple flame retardancy action of PDA (i.e., char formation + radical scavenging) enables flame retardant foams with a peak heat release rate (P-HRR) that is significantly reduced (up to 67%) relative to control foams, representing much better performance than many conventional additives reported in the literature at comparable or higher loadings.

Mechanically stable thermally cross linked poly(acrylic acid)/reduced graphene oxide aerogels - Ha, Heonjoo; Shanmuganathan, Kadhiravan; Ellison, Christopher J. (ACS Applied Materials & Interfaces, 2015)
Graphene oxide (GO) aerogels, high porosity (>99%) low density (similar to 3-10 mg cm(-3)) porous materials with GO pore walls, are particularly attractive due to their lightweight, high surface area, and potential use in environmental remediation, superhydrophobic and superoleophilic materials, energy storage, etc. However, pure GO aerogels are generally weak and delicate which complicates their handling and potentially limits their commercial implementation. The focus of this work Vas to synthesize highly elastic, mechanically stable aerogels that are robust and easy to handle without substantially sacrificing their high porosity or low density. To overcome this challenge, a small amount of readily available and, thermally cross-linkable poly(acrylic acid) (PAA) was intermixed with GO to enhance the mechanical integrity Of the aerogel without disrupting other desirable characteristic properties. This method is a simple straightforward procedure that does not include multistep or complicated chemical reactions, and it produces aerogels with mass densities of about 4-6 mg cm(-3) and >99.6% porosity-that can reversibly support up to 10 000 times their weight with full recovery of their original volume. Finally; pressure sensing capabilities were demonstrated and their oil absorption capacities were measured to be around 120 g oil per g aerogel(-1) which highlights their potential Use in practical applications.
Keywords: aerogels; environmental remediation; graphene; Nanocomposites; poly(acrylic acid)

Polyhedral oligomeric silsesquioxane-containing thiol-ene fibers with tunable thermal and mechanical properties - Fang, Yichen; Ha, Heonjoo; Shanmuganathan, Kadhiravan; Ellison, Christopher J. (ACS Applied Materials & Interfaces, 2016)
Polyhedral oligomeric silsesquioxanes (POSS) are versatile inorganic-organic hybrid building blocks that have potential applications as reinforcement nanofillers, thermal stabilizers, and catalyst supports for metal nano particles. However, fabrication of fibrous materials with high POSS content has been a challenge because of the aggregation and solubility limits of POSS units. In this paper, we describe a robust and environmentally friendly fabrication approach of inorganic-organic hybrid POSS fibers by integrating UV initiated thiol-ene polymerization and centrifugal fiber spinning. The use of monomeric liquids in this approach not only reduces the consumption of heat energy and solvent, but it also promotes homogeneous mixing of organic and inorganic components that allows integration of large amount of POSS (up to 80 wt %) into the polymer network. The POSS containing thiol-ene fibers exhibited enhanced thermomechanical properties compared to purely organic analogs as revealed by substantial increases in residual weight and a factor of 4 increase in modulus after thermal treatment at 1000 degrees C. This simple fabrication approach combined with the tunability in fiber properties afforded by tailoring monomer composition make POSS containing thiol-ene fibers attractive candidates for catalyst supports and filtration media, particularly in high-temperature and harsh environments.
Keywords: cross-linked fiber; enhanced thermomechanical properties; inorganic-organic hybrid fiber; POSS; reactive centrifugal spinning; thiol-ene photopolymerization

Thermal stimuli-responsive behavior of pyrene end-functionalized PDMS through tunable P–P interactions - Ha, Heonjoo; Shanmuganathan, Kadhiravan; Fei, Yunping; Ellison, Christopher J. (Journal of Polymer Science Part B-Polymer Physics, 2016)
Pyrene end-functionalized, telechelic poly(dimethyl siloxane) (PDMS) materials were synthesized and their response to different thermal stimuli was evaluated. The incorporation of pyrene end groups introduces strong pi-pi interactions that facilitated a broad range of thermally responsive properties, in some circumstances forming pyrene nanocrystals that serve as physical crosslinks leading to elastic materials. By synthesizing different chain lengths, samples exhibiting a 7 orders of magnitude change in storage modulus in response to thermal stimuli were produced by modifying only the end-groups (0.6 wt % of all polymer segments). Repeated thermal cycling during rheological experiments revealed that pi-pi interaction and crystallization/melting kinetics of pyrene chain-ends plays a key role in their thermal responsiveness. The properties of these materials were tuned by adding free pyrene, neat PDMS, or graphene oxide (GO) nanoparticles, making them attractive for many applications (e.g., tunable damping materials, heat/light sensors, conductive gels, or light repositionable adhesives). For example, nanocomposites containing 1 wt % GO caused the melting temperature for pyrene crystal domains to more than double, and even induced pyrene end-group crystallization in samples that did not exhibit crystals in neat form. It is hypothesized that these features originate from pi-pi interactions between pyrene ends and GO surfaces. (C) 2015 Wiley Periodicals, Inc.